Penerapan QR Code Untuk Sistem Absensi Siswa SMP Berbasis Web - Elin Herlina; Taufik Hidayatulloh (Jurnal Teknologi dan Informasi (JATI), 2017)
QR Code is a type of two-dimensional bar code in the form developed by Denso Wave, a division of Denso Co. Corporation, a perudahaan in Japan, which was published in 1994. Barcode is a symbol marking the real object made of sticks pattern of black and white in order manage computer is easy to recognize a good student attendance data is needed to be able to provide ease in generating student attendance data and is one of the important factors in managing a good attendance data. Management of student attendance by using a QR Code-based Web is an application that will be built in "SMP Negeri 11 of Sukabumi" because attendance is still used is conventional systems, such as pengabsensian with books attendance and report absences still slow, so it can hinder time , to overcome the above problems, the authors propose a way of solving that is the making of a computer application which is expected with this system can reduce and minimize errors and problems that occur. QR Code is a type of two-dimensional bar code in the form developed by Denso Wave, a division of Denso Co. Corporation, a perudahaan in Japan, which was published in 1994. Barcode is a symbol marking the real object made of sticks pattern of black and white in order manage computer is easy to recognize a good student attendance data is needed to be able to provide ease in generating student attendance data and is one of the important factors in managing a good attendance data. Management of student attendance by using a QR Code-based Web is an application that will be built in "SMP Negeri 11 of Sukabumi" because attendance is still used is conventional systems, such as pengabsensian with books attendance and report absences still slow, so it can hinder time , to overcome the above problems, the authors propose a way of solving that is the making of a computer application which is expected with this system can reduce and minimize errors and problems that occur.Keywords : QR Code, Attendance, Web